Transfer of transuranium elements along the food chain lichen-reindeer-man – A review of investigations in Finnish Lapland - Paatero, Jussi; Salminen-Paatero, Susanna (Journal of Environmental Radioactivity, 2021)
Following the atmospheric nuclear tests in the '50s and early '60s radioecological research on the (sub)arctic food chain lichen-reindeer/caribou-man was initiated in Finland among other northern countries. The enrichment of radionuclides in this food chain can lead to exceptionally high body burdens among the indigenous Sami and Inuit populations consuming large quantities of the meat and edible organs of reindeer and caribou. In Finland, first fission and activation products and natural radionuclides were studied but in the early 1970s' the investigations concerning transuranium elements were started. These studies have continued to the present as also the effects of the Chernobyl accident on the existence of neptunium, plutonium, americium and curium isotopes in the environment of northern Finland have been investigated. In addition to radioactivity measure-ments detailed dietary surveys were performed among the reindeer herders and other Sami persons to assess the human intake of radionuclides by ingestion. The main aim of this literature review is to summarize the obtained data concerning transuranium elements in the food chain lichen-reindeer-man in northern Finland but also some supporting data is included. Peer reviewed